2020
DOI: 10.1016/j.dib.2020.106447
|View full text |Cite
|
Sign up to set email alerts
|

Data on the generation of two Nr2e3 mouse models by CRISPR / Cas9D10A nickase

Abstract: NR2E3 encodes an orphan nuclear receptor that plays a dual function as both transcriptional activator and repressor in photoreceptors, being necessary for cone fate inhibition as well as rod differentiation and homeostasis. Mutations in this gene cause retinitis pigmentosa (RP), enhanced S cone syndrome (ESCS) and Goldmann-Favre syndrome (GFS). There is one reported Nr2e3 isoform that contains all 8 exons and a second –previously unreported– shorter isoform, which only spans t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The efficiency of paired nCas9 for precise mammalian genome editing has been characterized in vitro (Trevino and Zhang, 2014 ; Cho et al, 2014 ). It has also been employed in mouse zygotes for gene functionality research (Aísa-Marín et al, 2020 ; Shen et al, 2014 ) and the generation of animal models (Aísa-Marín et al, 2020 ; Domènech et al, 2020 ). In a recent study, hereditary tyrosinemia was successfully corrected in rats using a single nCas9 together with a homology template carried by two independent adenoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of paired nCas9 for precise mammalian genome editing has been characterized in vitro (Trevino and Zhang, 2014 ; Cho et al, 2014 ). It has also been employed in mouse zygotes for gene functionality research (Aísa-Marín et al, 2020 ; Shen et al, 2014 ) and the generation of animal models (Aísa-Marín et al, 2020 ; Domènech et al, 2020 ). In a recent study, hereditary tyrosinemia was successfully corrected in rats using a single nCas9 together with a homology template carried by two independent adenoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…The Rd7 mouse harbors spontaneous mutations in Nr2e3, which cause a retinal degeneration phenotype reminiscent of the ESCS patients (Iannaccone et al, 2021). However, key rod function genes such as the light-sensitive protein rhodopsin (Rho) are expressed in the Nr2e3-deficient mouse retina (Aísa-Marín et al, 2023;4 Corbo and Cepko, 2005;Haider et al, 2006;Iannaccone et al, 2021), in contrast to the complete loss of rod function observed in ESCS patients. As the mouse has a rod-dominant retina lacking a conerich macula (Volland et al, 2015), and the requirement of core rod transcription factors for rod specification is known to vary in other vertebrates (Oel et al, 2020), the precise regulatory processes governing rod and cone photoreceptor specification and maturation may differ between species.…”
Section: Introductionmentioning
confidence: 99%
“…We previously generated two Nr2e3 mouse models using CRISPR-Cas9 editing to delete different domains encoded in the last exon (Aísa-Marín et al, 2020b, 2020a. The Nr2e3 ∆27 model -carrying a homozygous in-frame deletion that ablates the dimerization domain-shows an ESCS-like phenotype, with profound but non-progressive alterations in retinal function (Aísa-Marín et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%